A File Encoding Using A Combination of Advanced Encryption Standard, Cipher Block Chaining and Stream Cipher In Telkom Region 4 Semarang - Lekso Budi Handoko; Andi Danang Krismawan (Journal of Applied Intelligent System, 2021)
The increase in significant advances in information technology greatly provides comfort and convenience in managing data. This convenience is what makes people who are not responsible for using it as a crime such as hacking, cracking, phishing, and so on. In Telkom Region 4 Semarang, there is a container where there are important company data such as customer data. Customer data is very important and the contents of the data must be kept confidential. The company has experienced significant losses due to information leakage due to negligence in the last 5 years. For this reason, data security is necessary so that data is safe and is not misused. This study applies the Advance Encryption Standard algorithm - Cipher Block Chaining (AES-CBC) and Stream cipher in order to secure data so as to reduce the risk of data theft by telecom subscribers. Based on the average avalanche effect value of AES-CBC and a stream cipher of 49.34%, this shows that the AES-CBC and Stream Cipher encrypted files are difficult to crack so that data confidentiality is well maintained.